Lycopene reduces ovarian tumor growth and intraperitoneal metastatic load - Holzapfel, Nina Pauline (Am J Cancer Res, 2017)
Mutagens like oxidants cause lesions in the DNA of ovarian and fallopian tube epithelial cells, resulting in neoplastic transformation. Reduced exposure of surface epithelia to oxidative stress may prevent the onset or reduce the growth of ovarian cancer. Lycopene is well-known for its excellent antioxidant properties. In this study, the potential of lycopene in the prevention and treatment of ovarian cancer was investigated using an intraperitoneal animal model. Lycopene prevention significantly reduced the metastatic load of ovarian cancer-bearing mice, whereas treatment of already established ovarian tumors with lycopene significantly diminished the tumor burden. Lycopene treatment synergistically enhanced anti-tumorigenic effects of paclitaxel and carboplatin. Immunostaining of tumor and metastatic tissues for Ki67 revealed that lycopene reduced the number of proliferating cancer cells. Lycopene decreased the expression of the ovarian cancer biomarker, CA125. The anti-metastatic and anti-proliferative effects were accompanied by down-regulated expression of ITGA5, ITGB1, MMP9, FAK, ILK and EMT markers, decreased protein expression of integrin α5 and reduced activation of MAPK. These findings indicate that lycopene interferes with mechanisms involved in the development and progression of ovarian cancer and that its preventive and therapeutic use, combined with chemotherapeutics, reduces the tumor and metastatic burden of ovarian cancer in vivo.